The Influence of Motivation and Work Discipline on the Performance of Employees of the Palembang Sekip Health Center - Andini Apriyanti; Siti Komariah Hildayanti; Try Wulandari (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to analyze the effect of work motivation and work discipline both partially and simultaneously on the performance of employees of Puskesmas Sekip Palembang. The data in this study were collected through distributing questionnaires to 64 respondents. The type of data in this study uses qualitative data and quantitative data. To see the extent of the accuracy and feasibility of the research variable instrument used validity and reliability tests, the data analysis technique used is multiple linear regression analysis models, with t tests and F tests. The results of the t test analysis in this study show that partially work motivation has a significant effect, and work discipline has a significant effect on employee performance at the Sekip Palembang Health Center. The results of the F test analysis and the coefficient of determination show that simultaneously work motivation and work discipline have a positive and significant influence on the performance of employees of the Palembang Sekip Health Center by 37.7 percent, while the remaining 63.3 percent is influenced by other factors outside the study. This shows that the higher the work motivation and work discipline, the higher the performance produced by the employees of the Palembang Sekip Health Center.